Effect of Four Different Initial Drying Temperatures on Biochemical Profile and Volatilome of Black Tea - Zaifa Shu; Huijuan Zhou; Limin Chen; Yuhua Wang; Qingyong Ji; Weizhong He (Metabolites)
Background: Black tea processing conditions significantly affect the final taste and flavor profiles, so researchers are now focusing on developing equipment and improving the appropriate processing conditions of major black tea varieties. Methods: Here, we tested the effect of four different initial drying temperatures, i.e., R65 (65 °C), R85 (85 °C), R105 (105 °C), and R125 (125 °C), on the sensory and biochemical profiles and volatilome of the black tea variety “Lishui wild” (LWV). Results: Our results indicate that both 85 and 105 °C are better than 65 and 125 °C for initial drying for 20 min. R105 had the highest sensory evaluation scores due to better shape, aroma, taste, leaf base, thearubigins, theanine, caffeine, and ratio of theaflavins + thearubigins to theaflavins. Both R85 and R105 had higher catechins than R65 and R125. The LWV volatilome consisted of esters (19.89%), terpenoids (18.95%), ketones (11.3%), heterocyclic compounds (9.99%), and alcohols (8.59%). In general, acids, aldehydes, amines, aromatics, ethers, hydrocarbons, phenols, sulfur compounds, and terpenoids accumulated in higher amounts in R85 and R105. The highly accumulated compounds in R105 were associated with green, fruity, sweet, woody, floral, hawthorn, mild, nutty, powdery, rose, and rosy flavors. The main pathways affected are secondary metabolites, sesquiterpenoid and triterpenoid biosynthesis, glycerolipid metabolism, zeatin biosynthesis, phenylpropanoid biosynthesis, ABC transport, glutathione metabolism, etc. Therefore, R105 can be used to achieve the optimal taste, flavor, and aroma of LWV. Conclusions: Overall, the presented data can be used by the tea industry for processing black tea with the most optimum volatile substances, catechins, theanine, amino acids, and other compounds.